Lift off to language and culture - Edgar, Patricia, 1937-; Andreacchio, Mario; Budds, Colin; Smith, Amanda; Smith, Stella; Australian Children's Television Foundation; Curriculum Corporation (Australia) ([Carlton, Vic.] : Australian Children's Television Foundation ; Curriculum Corporation, 1992)
Outlines how children learn language and the importance of the socio-cultural context in the development of effective language use. Video consists of excerpts from the Lift off program that have a particular application to the language acquisition of young children in our multicultural society. Shows children speaking, planning, cooperating and celebrating from different cultural perspectives.
Book of same title written by Stella Smith. Title on the cover of both this & video: Lift-off.
Keywords: Education, Primary -- Australia -- Curricula; Television programs for children -- Australia; Television in primary education -- Australia; Language arts (Primary); Cultural pluralism -- Study and teaching (Primary) -- Australia